Optimization and Comparative Economic Analysis of Standalone and Grid-Connected Hybrid Renewable Energy System for Remote Location - Jain, Siddharth; Sawle, Yashwant (Frontiers in Energy Research, 2021)
Due to rising population growth and economic development, there is indeed a growing demand for electricity. Both in aspects of generation and transmission, conventional power firms are striving to manage these demands. Moreover, the ubiquitous utilization of electricity and other power generators, which are mainly driven from fossil fuels, seems to have some limitations, like declining performance and restricted energy production. As a result, use of renewable energy sources is incredibly important. Decentralized power generation in remote regions has become the primary requirement of society, based on renewable energy. Particularly in comparison with the electrification of urban areas, rural electrification is quite expensive. Microgrid’s development utilizing hybrid power is a potential solution for the electrification of rural regions where the transmission chain of network’s extension is unfeasible or inefficient. This research aims to structure a power generation model associated with different HRES combinations using a HOMER software application at a location in India. In the findings of this research, it has been observed that NPC, O&M, COEs, and RF of on-grid energy systems are better than off-grid energy systems. In the study, between eight hybrid system combinations, the lowest COE of 0.034 /kWh is obtained with the PV-WT-MH-GRID-CT system in the on-grid scenario. This analysis shows NPC, COE, O&M, and renewable fraction are sensitive to the variation in all the considered sensitivity parameters1,2,3,4.